Lipopolysaccharide (LPS) binding protein opsonizes LPS-bearing particles for recognition by a novel receptor on macrophages (The Rockefeller University Press, 1989)
Lipopolysaccharide binding protein (LBP) is an acute-phase reactant that binds bacterial LPS. We show that LBP binds to the surface of live Salmonella and to LPS coated erythrocytes (ELPS), and strongly enhances the attachment of these particles to macrophages. LBP bridges LPS- coated particles to macrophages (MO) by first binding to the LPS, then binding to MO. Pretreatment of ELPS with LBP enabled binding to MO, but pretreatment of MO had no effect. Moreover, MO did not recognize erythrocytes coated with LBP unless LPS was also added, thus suggesting that interaction of LBP with LPS results in a conformational change in LBP that allows recognition by MO. Binding of LBP-coated particles appears to be mediated by a receptor found on blood monocytes and MO but not on other leukocytes or umbilical vein endothelium. The receptor is mobile in the plane of the membrane since binding activity on MO was downmodulated upon spreading of cells on surfaces coated with LBP-LPS complexes. The receptor appears to be distinct from other opsonic receptors since downmodulation of CR1, CR3, Fc gamma RI, Fc gamma RII, and Fc gamma RIII with mAbs did not affect binding of LBP-coated particles, and leukocytes from CD18-deficient patients bound LBP-coated particles normally. Coating of erythrocytes with LBP-LPS complexes strongly enhanced phagocytosis observed in the presence of suboptimal amounts of anti-erythrocyte IgG. However, binding mediated by LBP-LPS complexes alone caused neither phagocytosis of the LBP-coated erythrocytes nor initiation of an oxidative burst. The results of our studies define LBP as an opsonin. During the acute phase, LBP can be expected to bind gram-negative bacteria and bacterial fragments and promote the interaction of coated bacteria with phagocytes.